Islamic finance : a practical guide - Ali, Rahail (United Kingdom Globe business publishing ltd, 2014)
This second edition features fully updated, insightful chapters by leading practitioners in Islamic financing and analyses market trends, key developments and structures for sukuk, syndications, funds, takaful, project financing and Islamic liquidity management.
Includes bibliographical references.
rua 23/06/15
Loans
Keywords: Finance (Islamic law); Financial institutions